Last Glacial Maximum and Last Glacial–Interglacial Transition pollen record from northern NSW, Australia: evidence for a humid late Last Glacial Maximum and dry deglaciation in parts of eastern Australia. (3rd July 2017) - Ellerton, D.; Shulmeister, J.; Woodward, C.; Moss, P.
ABSTRACT: This paper presents the results of a palynological investigation into the late Last Glacial Maximum (LGM) and last deglaciation (ca. 20 000–9000 cal a BP) from Little Llangothlin Lagoon, in the sub‐tropics of eastern Australia. The Lagoon held permanent water during the late LGM and early deglaciation but was intermittently dry during the late deglaciation. During the late LGM, local vegetation was dominated by a sub‐alpine herbfield but the significant presence of rainforest taxa in the pollen record indicates the survival of rainforest, rainforest margin or wet sclerophyll communities close to the site. By ca. 17 000 cal a BP, open Eucalyptus forest replaced the alpine herbfield vegetation indicating that warming had commenced. Rainforest taxa disappeared at this time but re‐appeared at the end of the deglaciation. The LGM conditions are consistent with a dominant circulation system whereby persistent high pressure over eastern Australia brings onshore easterlies to this region and maintains humid conditions along the east coast and highlands of the Great Dividing Range. This is similar to modern winter circulation but the persistence of rainforest and wet sclerophyll taxa suggests an increase in easterly flow over modern conditions during the LGM. Copyright © 2017 John Wiley & Sons, Ltd.